The Norton anthology of short fiction - Bausch, Richard; Bausch, Richard, 1945-; Cassill, R. V. (Ronald Verlin), 1919-2002. (New York : W.W. Norton, 2006)
From the Publisher: Revised by celebrated novelist and short-fiction writer Richard Bausch, this edition continues to offer the most exciting blend of contemporary and classic short stories in a portable format. In this Shorter Seventh Edition, 72 stories by 68 authors are lightly supplemented by a general introduction, biographical notes, and essays written for the benefit of beginning writers.
Chronological table of contents -- Preface -- Writing about fiction -- Stories -- I want to know why / Sherwood Anderson -- Death by Landscape -- Related: Atwood, Why do you write? / Margaret Atwood -- Sonny's blues / James Baldwin -- Gorilla, my love -- Related: Bambara, What is it I think I'm doing anyhow? / Toni Cade Bambara -- Snow / Ann Beattie -- Occurrence at owl creek bridge / Ambrose Bierce -- Pierre Menard, author of the Quixote / Jorge Luis Borges -- Miriam /Truman Capote -- Cathedral -- Related: Carver, From on writing / Raymond Carver -- Paul's case -- Related: Andrea Barrett on Paul's case / Willa Cather -- Enormous radio / John Cheever -- Lady with the dog -- Related: Chekhov, Letter to DV Grigorovich -- Letter to A S Suvorin / Anton Chekhov -- Story of an hour / Kate Chopin -- Heart of darkness -- Related: Conrad, Preface to the nigger of the "Narcissus'' -- Letter to Barrett H Clark -- Barry Hannah on heart of darkness -- C P Sarvan, Racism and the heart of darkness / Joseph Conrad -- Continuity of parks / Julio Cortazar -- Open boat -- Related: Crane, Letter to John Northern Hiliard -- Allan Gurganus on the open boat -- Charles C Walcutt, [Stephen Crane: Naturalist] / Stephen Crane -- Wall of fire rising / Edwidge Danticat -- Intruder / Andre Dubus -- King of the bingo game -- Related: Ellison, an interview / Ralph Ellison -- Matchimanito / Louise Erdrich -- Barn burning -- Rose for Emily -- Related: Faulkner, an interview / William Faulkner -- Babylon revisited / F Scott Fitzgerald -- Great falls -- Related: Ford on Bharati Mukherjee's -- Management of grief / Richard Ford -- Handsomest drowned man in the world / Gabriel Garcia Marquez -- Yellow wallpaper / Charlotte Perkins Gilman -- Soldier's embrace / Nadine Gordimer -- Young Goodman Brown -- Related: Edgar Allan Poe, Review of Hawthorne's twice told tales / Nathaniel Hawthorne -- Hills like white elephants -- Related: Frederick Busch on hills like white elephants -- Hemingway, an interview / Ernest Hemingway -- Conscience of the court / Zora Neale Hurston -- Araby -- Dead -- Related: C C Loomis, Jr., structure and sympathy in Joyce's "The dead'' / James Joyce -- Metamorphosis -- Hunger artist -- Related: Stanley Corngold, Kafka's the metamorphosis: metamorphosis of the metaphor -- Kafka, Letter to Max Brod / Franz Kafka -- White horse / Yasunari Kawabata -- Girl / Jamaica Kincaid -- Horse dealer's daughter -- Rocking horse winner -- Related: Lawrence, Why the novel matters / DH Lawrence -- Ones who walk away from Omelas / Ursula K Le Guin -- Angel Levine / Bernard Malamud -- Disorder and early sorrow -- Related: Mann, letter to Paul Amann / Thomas Mann -- Bliss / Katherine Mansfield -- Shiloh / Bobbie Ann Mason -- Adventure in Paris -- Related: Maupassant, the novel / Guy De Maupassant -- Why I like country music / James Alan Mcpherson -- Bartleby, the Scrivener -- Related: Leo Marx, Melville's parable of the walls / Herman Melville -- Management of grief -- Related: Richard Ford on the Management of grief -- Mukherjee, a four-hundred-year-old woman / Bharati Mukherjee -- Royal beatings -- Related: Munro, What is real? / Alice Munro -- Signs and symbols / Vladimir Nabokov -- How I contemplated the world from the Detroit house of correction and began my life over again -- Related: Oates, the Art and craft of revision / Joyce Carol Oates -- Things they carried / Tim O'Brien -- Good man is hard to find -- Everything that rises must converge -- Related: O'Connor, the Nature and aim of fiction -- Lee Smith on a good man is hard to find / Flannery O'Connor -- Guests of the nation -- Related: Edward P Jones on Guests of the nation / Frank O'Connor -- O yes / Tillie Olsen -- Fall of the house of usher -- Related: Poe, the Philosophy of composition -- Poe, Review of Hawthorne's twice told tales -- Richard Wilbur, the House of Poe / Edgar Allan Poe -- Jilting of Granny Weatherall -- Related: Porter, an interview / Katherine Anne Porter -- Conversion of the Jews / Philip Roth -- Gimpel the fool / Isaac Bashevis Singer -- Chrysanthemums / John Steinbeck -- Rules of the game / Amy Tan -- Secret life of Walter Mitty -- Related: Thurber, an interview / James Thurber -- Death of Ivan Ilych -- Related: Gary Saul Morson, the Reader as Voyeur: Tolstoi and the poetics of didactic fiction -- Tolstoy, What is art? / Leo Tolstoy -- A & P -- Related: Updike, Accepting the Howells medal / John Updike -- Moths / Helena Maria Viramontes -- Everyday use / Alice Walker -- Blackberry winter / Robert Penn Warren -- Worn path -- Related: Susan Dodd on a Worn path -- Welty, an interview / Eudora Welty -- Use of force / William Carlos Williams -- In the garden of the North American martyrs / Tobias Wolff -- Kew gardens / Virginia Woolf -- Man who was almost a man / Richard Wright -- Writers On Writing -- Why do you write? / Margaret Atwood -- What is it I think I'm doing anyhow? / Toni Cade Bambara -- Letter to a young writer / Richard Bausch -- from On writing / Raymond Carver -- Letter to DV Grigorovich, March 28, 1886 -- Letter to AS Suvorin, October 27, 1888 / Anton Chekhov -- Preface to the Nigger of the "Narcissus'' -- Letter to Barrett H Clark, May 14, 1918 / Joseph Conrad -- Letter to John Northern Hiliard, February 1895 [?] / Stephen Crane -- Interview / Ralph Ellison -- Interview / William Faulkner -- Interview / Ernest Hemingway -- Letter to Max Brod, July 5, 1922 / Franz Kafka -- Why the novel matters / D H Lawrence -- Letter to Paul Amann, September 10, 1915 / Thomas Mann -- Novel / Guy De Maupassant -- Four-hundred-year-old woman / Bharati Mukherjee -- What is real /Alice Munro -- Art and craft of revision / Joyce Carol Oates -- Nature and aim of fiction / Flannery O'Connor -- Philosophy of composition / Edgar Allan Poe -- Interview / Katherine Anne Porter -- Interview / James Thurber -- What is art? / Leo Tolstoy -- Accepting the Howells medal / John Updike -- Interview / Eudora Welty -- Writing Fiction -- Reviews And Commentaries -- Willa Cather's "Paul's case'' / Andrea Barrett -- Ernest Hemingway's "Hills like white, elephants'' / Frederick Busch -- Kafka's the Metamorphosis: metamorphosis of the metaphor / Stanley Corngold -- Eudora Welty's "A worn path'' / Susan Dodd -- Bharati Mukherjee's "The management of grief'' / Richard Ford -- Stephen Crane's "The open boat / Allan Gurganus -- Joseph Conrad's Heart of darkness / Barry Hannah -- Frank O'Connor's "Guests of the nation'' / Edward P Jones -- Structure and Sympathy in Joyce's "The dead'' / C C Loomis, Jr -- Melville's Parable of the walls / Leo Marx -- Reader as voyeur: Tolstoi and the poetics of didactic fiction / Gary Saul Morson -- Review of Hawthorne's twice told tales / Edgar Allan Poe -- Racism and the heart of darkness / C P Sarvan -- Flannery O'Connor's "A good man is hard to find'' / Lee Smith -- [Stephen Crane: Naturalist] / Charles C Walcutt -- From the house of Poe / Richard Wilbur -- Glossary of critical terms -- Permissions acknowledgments -- Index of titles.
Includes bibliographical references and index.
Keywords: Short stories; Literatura inglesa -- Colecciones; Literatura estadounidense -- Colecciones; Autoras inglesas; Autoras estadounidenses